2020
DOI: 10.1093/ije/dyaa134
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for positive and negative COVID-19 tests: a cautious and in-depth analysis of UK biobank data

Abstract: Background The recent COVID-19 outbreak has generated an unprecedented public health crisis, with millions of infections and hundreds of thousands of deaths worldwide. Using hospital-based or mortality data, several COVID-19 risk factors have been identified, but these may be confounded or biased. Methods Using SARS-CoV-2 infection test data (n = 4509 tests; 1325 positive) from Public Health England, linked to the UK Biobank … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
151
5
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(178 citation statements)
references
References 41 publications
18
151
5
4
Order By: Relevance
“…Compared to a healthy weight, overweight, obese and severely obese (BMI ⩾35) subjects had a 1.31-, 1.55-, or 1.57-fold higher probability of SARS-CoV-2 positivity [68]. Chadeau-Hyam et al reported that severe obesity is independently associated with the risk of obtaining COVID-19 with an odds ratio >1.05 by analysing the data from Public Health England [69]. In our meta-analysis, patients with a BMI ⩾30 had a 1.39 times higher chance of having COVID-19 than those with a healthy weight, which was in line with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to a healthy weight, overweight, obese and severely obese (BMI ⩾35) subjects had a 1.31-, 1.55-, or 1.57-fold higher probability of SARS-CoV-2 positivity [68]. Chadeau-Hyam et al reported that severe obesity is independently associated with the risk of obtaining COVID-19 with an odds ratio >1.05 by analysing the data from Public Health England [69]. In our meta-analysis, patients with a BMI ⩾30 had a 1.39 times higher chance of having COVID-19 than those with a healthy weight, which was in line with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…We considered six categories of variables potentially associated with COVID-19 mortality: demographic, social, health risk, biological, medical, and environmental factors [ 32 ] (Supplementary Methods). Demographic variables were age, sex and ethnicity (White, Black, Other).…”
Section: Study and Methodsmentioning
confidence: 99%
“…An enormous literature has evolved over the course of the pandemic on individual predictors of COVID-19 related outcomes (e.g. Chadeau-Hyam et al, 2020; Williamson et al, 2020). A smaller body of work has also emerged looking the area-level predictors of COVID-19 outcomes and exposures (e.g.…”
Section: Introductionmentioning
confidence: 99%